Groundhog day - Albert, Trevor; Ramis, Harold; Columbia Pictures ([California Columbia Pictures, 1993)
A romantic comedy about a weatherman caught in a personal time warp on the worst day of his life.
VHS
Story by Danny Rubin ; screenplay by Danny Rubin and Harold Ramis ; produced by Trevor Albert and Harold Ramis ; directed by Harold Ramis.
Bill Murray, Andie MacDowell.
Keywords: Groundhog Day; Comedy films; Feature films